Interleukin (IL)-12 and IL-18 Synergize to Promote MAIT Cell IL-17A and IL-17F Production Independently of IL-23 Signaling - Cole, Suzanne; Murray, Janine; Simpson, Catherine; Okoye, Remi; Tyson, Kerry; Griffiths, Meryn; Baeten, Dominique; Shaw, Stevan; Maroof, Asher (Frontiers in Immunology, 2020)
IL-23 is considered a critical regulator of IL-17 in Th17 cells; however, its requirement for inducing IL-17 production in other human immune subsets remains incompletely understood. Mucosal associated invariant T (MAIT) cells uniformly express retinoic acid receptor-related orphan receptor gamma t (RORγt) but only a minor population have been shown to produce IL-17A. Here we show that IL-17F is the dominant IL-17 isoform produced by MAIT cells, not IL-17A. For optimal MAIT cell derived IL-17A and IL-17F production, T cell receptor (TCR) triggering, IL-18 and monocyte derived IL-12 signaling is required. Unlike Th17 cells, this process is independent of IL-23 signaling. Using an in vitro model of skin inflammation, we demonstrate that dual neutralization of both IL-17A and IL-17F resulted in greater suppression of inflammatory proteins than inhibition of IL-17A alone. Finally, we extend our findings by showing that other innate-like lymphocytes such as group 3 innate lymphoid cells (ILC3) and gamma delta (γδ) T cells are also capable of IL-23 independent IL-17A and IL-17F production. These data indicate both IL-17F and IL-17A production from MAIT cells may contribute to tissue inflammation independently of IL-23, in part explaining the therapeutic disconnect between targeting IL-17 or IL-23 in certain inflammatory diseases.